Performance Analysis of a High Voltage DC (HVDC) Transmission System under Steady State and Faulted Conditions - M. Zakir Hossain; Md. Kamal Hossain; Md. Alamgir Hossain; Md. Maidul Islam (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The modern High Voltage Direct Current (HVDC) transmission technology depends on the development of power electronics based on the semiconductor devices. This paper represents a simple model of HVDC transmission system in which the converter and filter have been designed to increase stability of power transmission. The HVDC transmission system has been proposed on the basis of simulation studies using MATLAB software package (Simulink Model). Using this model, current - voltage (C-V) characteristics have been simulated for steady state condition. It has also been studied for different fault conditions.  With the proposed strategy the HVDC system can provide useful and economical way to transmit electric power over the long distance, thereby improving the bulk transmission of electric power and power system stability.